Tectonics of Formalism in the Art Criticism of the Period of Methodological Oddities: On Exhibitions, Anthology and Discussions of the Second Half of the 2010s - Boiko, Aleksei G. (Actual Problems of Theory and History of Art, 2017)
The article is devoted to the three-volume edition of The Formal Method. An Anthology of Russian Modernism which conforms to the demand of the contemporary art scene for structures and forms that reveal the actual visual artistic thinking of the 21st century; the contents of the anthology can be grasped from theinside of the actual artistic process. This work of the international collective of authors can be described, in general, as a clever book of oddities and readers surprises, which corresponds to the attitude of Russian formalism.The integrity and the appearance of the book was achieved by the design and the will of Professor S. Oushakin, the scientific editor of the anthology. The book shows the uneven development and the impact of the method of formalism in the theory and the history of fine arts, literary studies, and linguistics. Russian art historians are ready to reinterpret the formal method and include its main concepts in the active thesaurus. The formal method is represented on the pages of the reviewed book as a cultural practice with a wide range of applications. Its specificity is disclosed in the light of four interpretations of the concept of tectonics, identified by K. Rombergduring the research of Aleksei Gan’s activities. The article considers the formal method as the protection of a researcher in the field of ideology and the means of understanding artistic phenomena and practices, although this term is not associated with formalism in art and art history. It has been concluded that the symptoms of the pragmatic revitalization of the formal method can be detected at the present time.